PERLINDUNGAN KONSUMEN TERHADAP INFORMASI DIET DALAM BUKU PROGRAM DIET YANG DITULIS OLEH BUKAN AHLI GIZI - Melati Ramadhani Suari; Inosentius Samsul (Institut Pendidikan Tapanuli Selatan, 2023)
Every human being certainly has a desire in each of them, including the desire to have an ideal body. When you want to get the ideal body, humans will go on a diet. Not a few people who are successful on their diet share their diet program through social media and even write it down in a book that contains information about the diet program. Regarding diet information in the book can come from someone who is not a nutritionist. However, the diet that is carried out by one person does not always have a positive impact on others, resulting in losses. In this study, we want to find out how the legal protection for consumers who are harmed by buying a book about the diet program from someone who is not a nutritionist in terms of Law Number 8 of 1999 concerning Consumer Protection and the responsibility of the author of the book. The method used in this paper is normative juridical by using a statutory approach to answer the problems in this research. Every consumer has the right to get comfort, security, and safety for the goods and/or services he uses, so writers who write books must of course write their books clearly, correctly, and honestly. In addition, the author of the book must also complete the book or work he wrote and provide compensation to consumers who suffer losses due to the diet program written.